Removal of Cadmium (II) from Aqueous Solution through Adsorption using Wood Biochar: Kinetics and Isotherms Studies - H. Lalhruaitluanga; Lalremruata Hauhnar (Recent Developments in Chemistry and Biochemistry Research Vol. 8, 2024)
Removal of cadmium ions through adsorption has been investigated by locally available wood biochar. The motivations of the present study were to investigate the application of this wood biochar in the field of environmental problems, so that wood biochar would be more valuable for the community. Freundlich, Langmuir, Temkin, Redlich-Peterson, Sips, Flory-Huggins, Fowler-Guggenheim, and Harkin-Jura isotherms were used to elucidate the adsorption mechanism. Similarly, pseudo-first-order, Pseudo-second order, Intra-particle diffusion, and liquid film diffusion models were used to study the kinetics of adsorption. The sorption process is favorable with a monolayer formation and predominantly physical adsorption when the equilibrium is attained. The negative value of Gibbs free energy (\(Δ\)Go) indicates that the adsorption process is thermodynamically spontaneous and feasible. The presence of repulsion between the adsorbed molecules was also confirmed. The maximum adsorption capacity (qmax) was 28.57 mg/g. The kinetics of the adsorption process follows Pseudo-second order and is also controlled by diffusion through the liquid film. It also confirms the existence of boundary layer influence by Weber and Morris intraparticle diffusion. From these studies, the wood biochar could be used as an adsorbent for the efficient treatment of Cd (II) from an aqueous solution.